Manatee (Trichechus manatus manatus) Watching Swallow Caye,Belize - Sánchez C., Esther N. (Zamorano: Escuela Agrícola Panamericana, 2014., 2014)
Sánchez Chuc, Esther Naomi. 2002. Manatee (Trichechus manatus manatus) Watching at Swallow Caye, Belize. Special Project of the Engineer program in Socioeconomic Development and Environment, Zamorano. 43p. Belize is the Caribbean country that harbors the highest population of the Antillean Manatee (Trichechus manatus manatus). This docile and harmless mammal is an endangered species and is listed in the Appendix 1 of CITES. In Belize, manatees are also protected by the Wildlife Protection Act of 1981. However, there is great concern since the population of this species is decreasing, and one of the main reasons is human activities. This includes the increased high-speed boat traffic that causes injuries or even death from collisions, the loss of suitable habitat, which is a result of the tourism development projects, pollution and harassments among others. The observation of manatees in their natural habitat in this country is a tour activity that is rapidly growing. Presently, tours are being offered in destinations such as Caye Caulker, San Pedro, and Gales Point among others. Among the many areas that are habituated by these creatures, Swallow Caye is the most important site used for tourism, and it is also a key nursing and feeding site, therefore containing a very healthy population. This mangrove island is visited by an estimated 20-75 tourists per day. This study defines a profile of the tourists and tour guides who depart from the island of Caye Caulker to realize manatee tours. Additionally it gives a brief description of the tour, the behavior and conduct of both tour guides and tourists and the main reasons why visitors of this island choose manatee watching in Belize.